Safety of autonomous vehicles: what are the insights from experienced industry professionals? - Caulfield, Brian (My University, 2021)
Many drivers support the push towards the automation of transportation. Technology and automotive companies, the general public, and governments are all seen as the main groups pushing the automation revolution forward. The key to this revolution's success will rest with the perception of the professionals in the field as their perception will affect the way that Autonomous Vehicles (AVs) are adopted. This study surveyed 185 experienced industry professionals to gather their comments and opinions on AVs' purported safety benefits and drawbacks. The results in this paper illustrate that the ‘incorrect understanding of the surrounding objects by AVs’ could be the most significant technical concern and may lead to accidents. Some professionals had concerns about trusting the AVs’ safe operation without steering wheels, while some others believed that there is a chance that having steering wheels may increase safety concerns. The findings also suggest that while AVs might reduce the number of accidents, this may not necessarily be the case for the severity of any accidents. The severity may remain unchanged or even increase as a result of the adoption of AVs. This paper's results show that the majority of the professionals consulted agreed that AVs have the potential to increase road safety significantly. However, the consensus was that more research and testing is needed in this field.
PUBLISHED
Keywords: Autonomous vehicles; Safety; Expert opinion; Smart & Sustainable Planet; Accessibility; Transport